CORRELATION AUTOMOTIVE ACHIEVEMENT LEARNING AND DISCIPLINARY OF LEARNING WITH LEARNING READINESS WITH THE PRACTICE OF INDUSTRIAL ENGINEERING CLASS XI LIGHT VEHICLE VOCATIONAL HIGH SCHOOL MA'ARIF NANGGULAN KULON PROGO - Sri Aji Gularko; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of the study (1) To determine the correlation between the learning achievement of vocational automotive industry working practices with readiness class XI student of Light Vehicle Technical Vocational High School Ma'Arif Nanggulan Kulon Progo Academic Year 2013/2014; (2) To determine the correlation between the discipline of learning the practice of industrial work readiness class XI student of Light Vehicle Technical Vocational High School Ma'Arif Nanggulan Kulon Progo Academic Year 2013/2014; (3) To determine the correlation between learning achievement and discipline automotive vocational learning with practical work readiness class XI student industry Light Vehicle Technical Vocational High School Ma'Arif Nanggulan Kulon Progo Academic Year 2013/2014. This research was conducted at the Vocational School Ma'Arif Nanggulan Kulon Progo academic year 2013/2014 in the second semester. The population in this study were all students of class XI Light Vehicle Engineering, amounting to 108 students and this study using simple random sampling with harry king nomogram to obtain samples and 88 respondents were randomly selected by lottery. This research is correlational and ex post facto categorized. Questionnaire data collection techniques and documentation of learning achievement. The validity of the items were obtained from the product moment correlation. About the reliability of the formula obtained by alpha and declared reliable. Before the data were analyzed first tested the normality test is prerequisite analysis, linearity test, and test intercorrelations. Analysis using a simple correlation analysis and multiple correlation analysis. Based on the analysis of the results obtained the following results: (1) There is a positive and significant correlation between automotive vocational learning achievement (X1) with the readiness of the industry work practices (Y) class XI student Lightweight Vehicle Engineering Vocational School Ma'Arif Nanggulan Kulon Progo Year Doctrine 2013/2014; (2) There is a positive and significant correlation between the discipline of learning (X2) the readiness of the industry work practices (Y) class XI student Lightweight Vehicle Engineering Vocational School Ma'Arif Nanggulan Kulon Progo Academic Year 2013/2014;; (3) There is a positive and significant correlation learning achievement of vocational automotive (X1) and the discipline of learning (X2) together with the readiness of the industry work practices (Y) class XI student Lightweight Vehicle Engineering Vocational School Nanggulan Kulon Progo Maarif School Year 2013/2014.